Hipertensi Kronis Superimposed Preeklampsia dengan Impending Eklampsia dan Partial HELLP Syndrome - Dila Aulia; Nurul Islamy; Ade Yonata (CV. Jasa Sukses Abadi, 2020)
Hypertension in pregnancy is defined as systolic blood pressure of 140 mmHg or more or diastolic blood pressure of 90 mmHg or more. Preeclampsia is a new onset hypertension (blood pressure> 140 mmHg systolic and / or> 90 mmHg diastolic) after 20 weeks and proteinuria or in the absence of proteinuria. Chronic hypertension with superimposed preeclampsia is a chronic hypertension sufferer who has preeclampsia. Ten million women worldwide experience preeclampsia every year. Of these cases, 7,600 pregnant women die each year due to preeclampsia and related hypertension disorders. Preeclampsia accompanied by prodomal sign is called impending eclampsia. HELLP syndrome is a collection of symptoms that include hemolysis, elevated liver enzymes, and platelet counts that are less than the lower limit. The method used is a case report with analysis of primary data obtained from symptoms, physical examination and laboratory examination showing hemoglobin 11.2 g / dL, platelets 156,000 / µL, lactate dehydrogenase (LDH): 687 / µL and urine examination showed 500 mg results / dL. Ultrasonography (USG) on 26 October 2019 obtained a single live fetal head presentation, 26-27 weeks gestation, fetal weight 976 grams, congenital hydrocephalus abnormalities, sufficient amniotic fluid. Ultrasound on 04/10/2019 found a single fetus alive head presentation, 30 weeks gestation, congenital hydrocephalus abnormalities, normal membranes. There are risk factors associated with the onset of preeclampsia in these patients, namely a history of hypertension, old age, and BMI. In this case expectative management was chosen because in patients with preterm pregnancy <34 weeks.